Local Goverment Offices, Starnberg Germany - Ryman, Eve; Auer + Weber (1991)
Sobre las oficinas de la municipalidad de Starnberg por Auer & Weber.
Keywords: MUNICIPALIDADES; ALEMANIA; EDIFICIOS PUBLICOS; STARNBERG; AUER + WEBER; AUER, FRITZ; WEBER, CARLO; EDIFICIOS DE OFICINAS